Development of a Short Pulse Broadband and Narrow Linewidth Ultraviolet Laser Using Ce:LiCAF Crystal - Duong, Pham Van; Tu, Nguyen Xuan; Diep, Nguyen Van; Pham, Minh Hong; Sarukura, Nobuhiko; Cadatal-Raduban, Marilou (Communications in Physics, 2019)
We report the successful development of an all-solid state laser based on a Czochralski method-grown cerium-doped lithium calcium aluminum fluoride (Ce3+:LiCaAlF6 or Ce:LiCAF) crystal as the gain medium. Results for the broadband, narrow linewidth and short pulse laser emission are obtained by pumping the crystal with 7 ns pulses from the fourth harmonics (266 nm) of a Nd:YAG laser operating at 10 Hz. The effects of output coupler reflectivity, resonator length and pump energy on the laser pulse duration were explored. With broadband configuration, a maximum output pulse energy of 3.4 mJ and a slope efficiency of about 33% were achieved. By optimizing the parameters of the resonator and pump laser energy, 450 ps UV laser pulses were generated from resonator transient conditions of low-Q and short resonator under a near threshold pump energy. With narrow linewidth configuration, where the end mirror is replaced by a grating, tunability from 281 nm to 299 nm is also achieved with a linewidth of about 0.2 nm.